2019
DOI: 10.3126/bjhs.v3i3.22193
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Analysis of Olfactory Fossa Depth: A Tertiary Care Hospital Based Study

Abstract: Introduction: Computed tomogram (CT) of nose and paranasal sinuses provides the detailed knowledge of depth of olfactory fossa as per Keros' classification, which is important in endoscopic sinus surgery. Objective: To analyze the types and frequency of depth of olfactory fossa in Nepalese population. Methodology: This was a longitudinal study conducted from 1 May to 30 August 2018. Coronal CT scans of nose and paranasal sinuses were taken for analysis of olfactory fossa depth. The landmarks like i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In our study, the most common were Keros type II (71.9%), followed by Keros type I (17.8%), Keros type III (10.3%). While a few studies reported the most common Keros type I [1,2,7,20,21], most studies were the most common type II [3][4][5]8,[13][14][15][17][18][19][22][23][24][25][26][27][28], consistent with our study. The distributions according to the Keros classification in the studies conducted in the Turkish population are presented in Table 6.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the most common were Keros type II (71.9%), followed by Keros type I (17.8%), Keros type III (10.3%). While a few studies reported the most common Keros type I [1,2,7,20,21], most studies were the most common type II [3][4][5]8,[13][14][15][17][18][19][22][23][24][25][26][27][28], consistent with our study. The distributions according to the Keros classification in the studies conducted in the Turkish population are presented in Table 6.…”
Section: Discussionsupporting
confidence: 90%
“…There is a lateral lamella of the cribriform plate (LLCP) to which it is articulated medially. LLCP is the area most susceptible to iatrogenic damage during endoscopic sinus surgery (ESS) because of its very thin bone structure [1,2]. ESS is a treatment method used in the treatment of chronic rhinosinusitis.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the most common OF type was type 2 on the right (51%) and left (45.5%) sides. Type 1 was more common in some studies (10,(19)(20)(21)(22)(23), while type 2 was more common (61%-76.1%) in other studies, including the current study (2, 4, 8, 12, 14, 24 -30). The highest incidence was reported in the study of Periyasamy et al (28), but the incidence was found to be higher (80% and 83.3% on the right and left side of control group, respectively) because they divided 120 patients into 4 groups as the right and left, case (with sinusitis) and control groups, and calculated the incidence over 30 samples each.…”
Section: Of Types According To Depth Measurementsmentioning
confidence: 40%
“…Patil et al (26) reported that the mean OF depth on the right and left sides was 5.3 mm and 5.42 mm, respectively. In the study by Murthy and Santosh (29), a mean OF depth of 5.21 mm was reported, while Naidu et al (30) reported median depths of 5.6 and 6 mm on the right and left sides, respectively; Shrestha et al (10) reported that OF on the right side was deeper. In the study by Lakhani et al (12), the highest depth of OF was reported as 6.543 and 6.2 mm on the right and left sides, respectively, in the 51-60 years age group.…”
Section: Of Types According To Depth Measurementsmentioning
confidence: 98%